Neurovascular Imaging - Saba, Luca
Neurovascular Imaging provides a venue for researchers and clinicians interested in neurovascular imaging techniques in health and disease. The journal publishes on a wide range of topics, including imaging in stroke, intracranial arterial circulation, vasculitis, intra- and extra-cranial vascular anatomy, and spine circulation. Neurovascular Imaging considers research on imaging protocols and techniques including, but not limited to, computed tomography (CT), magnetic resonance (MR), nuclear medicine (NM), molecular imaging (MI) and ultrasonographic imaging (US).